The effect of special exercises according to the principle of re-training in the development of kinesthetic perception among middle school students - Dr. Shaimaa Ali (physical education and sport sciences college for women/ Baghdad University, 2020)
The importance of research that has manifested in raising the level of perception and its different types for students in the intermediate stages of education using a method and principle from the principles of mathematical training science is repeated because of its great importance in building the correct motor side, in addition to delivering scientific information to trainers and teachers about the importance of this training to the teacher And the student in raising the level of perceptual-motor.  The research objectives were: 1- Preparing special exercises according to the principle of re-training in the development of kinesthetic perception among middle school students. 2- Knowing the effect of special exercises according to the principle of re-training in developing sensory-motor perception among middle school students. Conclusion : 1-Training according to the principle of repetition has scientific significance in promoting and developing perceptual-motor awareness among middle school students. 2- The development of perceptual-motor awareness raises the aesthetic of the technical performance of sports for middle school students. 3-Adopting training according to the principle of repetition in the physical education lesson because of its scientific importance in promoting and developing perceptual-motor awareness among middle school students. 4-The emphasis in the physical education lesson on sensory-motor perception increases the aesthetic performance of athletic sports among middle school students